The Design of Picture Book "Petualangan Onding" Containing Bugis Values for Early Childhood Character Education - Amalia Syahbani, Andi Feninda (VCD, 2024)
The rise of moral degradation caused by the waning of knowledge and application of human values ​​contained in Bugis culture (Sipakatau, Sipakakainge’, Sipakalebbi) continues to increase. Seeing this condition, the design of picture storybooks as a medium for visual communication and introduction of cultural values ​​as educational materials were carried out with characters and increasing segmented visual literacy for early children. The title of the picture storybook is "Petualangan Onding". Contains 14 pages and tells the story of a Bugis child named Onding and a monkey endemic to South Sulawesi named Upe who invites readers on an adventure to get to know the three ancestral values ​​of the Bugis tribe: Sipakatau, Sipakainge’, and Sipakalebbi. The work creation method is carried out in stages from data collection to the execution process. Data was collected by obtaining primary data from people closely related to the book "Petualangan Onding", and then secondary data from literature studies. The book design process uses visual elements such as colors with a refreshing color mood, typography from the font named “Amalia”, and the concept of flat design illustrations. These elements are mixed in such a way as to create a culture-based visual communication medium for early childhood learning and character education.